Leverage dan growth opportunity mempengaruhi nilai perusahaan melalui profitabilitas - Supami Wahyu Setiyowati; Jamal Abdul Naser; Rini Astuti (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2020)
A company's value is a reflection or good name of the company. The company value means a lot to investors and potential investors. This research aims to examine the effect of leverage and growth opportunity on corporate value through profitability. In this study, the populations of consumer goods companies listed on the Indonesia Stock Exchange in the 2015-2017 period are used. This study used 15 companies as samples. Data processing techniques using path analysis. The results of the leverage study have a negative effect on profitability. A high amount of debt reduces profits. Growth opportunity affects profitability. An increase in assets increases profits. Leverage has a negative effect on firm value. A high amount of debt reduces the value of the company. Growth opportunity has a positive effect on firm value. An increase in assets or sales increases the value of the company. Profitability has an effect on firm value. Profits increase firm value. The effect of leverage on firm value with profitability as an intervening variable is not proven. Profitability indirectly has no effect on the relationship between leverage and firm value. The effect of growth opportunity on firm value with profitability as an intervening is proven. Indirectly, profitability affects the relationships of growth opportunity and firm value. Companies must have the right strategy in terms of using funds from outside the company to increase company value.